The Roles of Teachers in Promoting 10th-Grade Students’ Learner Autonomy in Learning English Writing Skills at Trung Vuong High School - Linh Y Ta; Lan Hoang Tran (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
Grounded in Sociocultural Theory, this study investigated how teachers and tenth-grade students perceive five teacher roles: Instructor, Facilitator, Resource, Assessor, and Co-learner in promoting learner autonomy in English writing skills among tenth-grade students in one upper-secondary school in Vietnam. The study used a convergent design of mixed methods to gather data from 4 English teachers and 450 tenth-grade students. The comparison between 2 sets of perceptions showed that both teachers and students acknowledged the Instructor and Assessor roles for their contributions to the development of learner autonomy by giving formative feedback and structured direction. The Facilitator role was preferred by teachers but disapproved by students. Although students indicated positive responses to the Resource role, teachers found it ineffective because of students' passive use of materials. Both groups voiced discomfort regarding the Co-learner role's practicality in a teacher-centered society, making it the least desired option. These findings propose the need for contextually adapted, autonomy-supportive practices in Vietnamese EFL writing instruction.